2017
DOI: 10.1016/j.rboe.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Puddu osteotomy with or without autologous bone grafting: a prospective clinical trial

Abstract: ObjectivesTo test the hypothesis that autologous iliac bone grafts do not enhance clinical results and do not decrease complication rates in patients undergoing medial opening-wedge high tibial osteotomy.MethodsForty patients allocated in a randomized, two-armed, double-blinded clinical trial were evaluated between 2007 and 2010. One group received bone graft, and the other group was left without filling the osteotomy defect. The primary outcome was the Knee Society Score. Radiographic measurement of the front… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 20 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…20 The majority of loss of correction occurred in the first year, without any correlation between the degrees of loss of correction and subject characteristics. In Passarelli et al's study 22 both the BG and NF groups demonstrated a progressive loss of correction following 6 months of surgery and a follow-up of >4 years, but the loss was equal in both groups. In accordance with our pooled results, no loss of correction was observed due to the lack of graft.…”
Section: Failure and Complicationsmentioning
confidence: 90%
See 4 more Smart Citations
“…20 The majority of loss of correction occurred in the first year, without any correlation between the degrees of loss of correction and subject characteristics. In Passarelli et al's study 22 both the BG and NF groups demonstrated a progressive loss of correction following 6 months of surgery and a follow-up of >4 years, but the loss was equal in both groups. In accordance with our pooled results, no loss of correction was observed due to the lack of graft.…”
Section: Failure and Complicationsmentioning
confidence: 90%
“…Elsayed et al and Passarelli et al 21,22 reported a significant increase in the KSS in both the BG and NF group compared with the preoperative score; however, no significant difference was observed in the BG or NF group, which suggests that bone grafting does not affect the postoperative function of the knee joint following OWHTO. In addition, Zorzi et al's study 18 showed no statistically significant difference in the meantime to clinical bone union between the BG ( 15,16 also showed no difference in time to clinical or radiologic union between the groups.…”
Section: Clinical Outcome Assessmentmentioning
confidence: 92%
See 3 more Smart Citations